Determinant Factors Cross Generation Behavior on Halal Food Product: Empirical Evidence from Indonesia - Sukesti, Fatmasari; Nurcahyono, Nurcahyono; Budiman, Mamdukh; Ifada, Luluk Muhimatul (UNISSULA, 2024)
The purpose of this study is to add new knowledge about the determinants of factors influence the choice of halal food products in Indonesia in X, Y and Z generations. The exiting literature focusses on halal product with all consumers regardless of age. The determining variable uses subjective norms, level of religiosity, halal certificate and health awareness. This study uses the theory of planned behavior to explaining phenomena and relationships between variables. This research is also part of the development of previous research. The research used a sample of 400 respondents from each generation. The research was tested using multiple linear regression analysis and different tests and used the SPSS 25 statistical test tool. The result showed subjective norm variables had an ineffectually on commodity selection behaviour halal on gen X and gen Y. In contrast, in generation Z, subjective norms positively impacted the way of behaving variables chosen by halal products. The religiosity level variable positively impacts the demeanour of choosing halal products in the three generations. The different test results showed that the three generations of X, Y and Z have no differences in determining attitudes towards the selection of halal products, which are influenced by the four independent variables, with the average mean almost the same in each generation on each independent variable. The variable health consciousness positively impacts three generations on the behaviour of choosing halal products. In comparison, the variable halal certificate affects generations X and Y but does not impact generation Z. This research confirms the theory of planned behaviour in the intention to buy halal products. Furthermore, the intention to buy halal products from various generations is strongly influenced by subjective norms, a person's religious level and halal certification. Therefore, business actors whom regulators support need to pay attention to these various aspects.